Flexible epoxy novolac coatings: use of cardanol-based flexibilizers - Gour, Rajeshwari S.; Raut, Kundalik G.; Badiger, Manohar V. (Journal of Applied Polymer Science, 2017)
Flexible epoxy novolac coatings were developed by reacting an epoxy novolac resin, Poly[(phenylglycidyl ether)-co-formaldehyde] (PPGEF) with an amine curing agent, 4,4′-diamino-3,3′-dimethyldicyclohexyl methane (BMCHA), cardanol based reactive diluent (Cardolite NC-513) and two different cardanol-based flexibilizers (Cardolite NC-514 and Cardolite NC-547). The flexibilizer content was varied from 5 to 10% by weight of the resin. These resins were coated onto the stainless steel panels and tested for their gloss, cross-hatch adhesion, falling weight impact resistance, flexibility, abrasion, scratch hardness, solvent scrub resistance, and chemical resistance. The thermo-mechanical properties of these coatings were determined by TGA, DSC, DMTA, and tensile strength measurements. The cryofractured specimens were subjected to SEM analysis. The influence of structural differences of two flexibilizers on the coating properties was investigated. These coatings exhibited excellent properties and have great potential in industrial applications. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44920.